2010
DOI: 10.1037/a0020768
|View full text |Cite
|
Sign up to set email alerts
|

Media as social influence: Racial differences in the effects of peers and media on adolescent alcohol cognitions and consumption.

Abstract: Racial differences in the effects of peer and media influence on adolescents' alcohol cognitions and consumption were examined in a large-scale panel study. With regard to peer influence, results from cross-lagged panel analyses indicated that the relation between perceived peer Correspondence concerning this article should be addressed to Frederick X. Gibbons, Department of Psychological and Brain Sciences, 6207 Moore Hall, Dartmouth College, Hanover, NH 03755; or rick.gibbons@dartmouth.edu. Publisher's Discl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

7
86
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
4
3
3

Relationship

0
10

Authors

Journals

citations
Cited by 88 publications
(93 citation statements)
references
References 79 publications
7
86
0
Order By: Relevance
“…Therefore, although minority youth were more heavily exposed to advertising in the present study, they may be less receptive to it. This is in line with a number of other studies (Brown et al, 2006;Gibbons et al, 2010;Tanski et al, 2012). Much remains to be learned about whether, when, and why youth are more receptive to alcohol advertising to provide appropriate context for interpreting exposure rates.…”
Section: Discussionsupporting
confidence: 54%
“…Therefore, although minority youth were more heavily exposed to advertising in the present study, they may be less receptive to it. This is in line with a number of other studies (Brown et al, 2006;Gibbons et al, 2010;Tanski et al, 2012). Much remains to be learned about whether, when, and why youth are more receptive to alcohol advertising to provide appropriate context for interpreting exposure rates.…”
Section: Discussionsupporting
confidence: 54%
“…To our knowledge, only one study has examined racial differences in the influence of media and found that increased exposure to alcohol use in movies was a longitudinal predictor of alcohol consumption; however, these effects were much stronger for Caucasian adolescents than Black adolescents [95]. Thus, an important future direction is to replicate and extend work that examines if, how, and why alcohol marketing is more or less influential among ethnic minorities.…”
Section: Implications and Future Directionsmentioning
confidence: 99%
“…African American adolescents self-report lower levels of susceptibility to general peer influence, 11 and a separate body of work on substance use suggests that Caucasian youth may be more susceptible to peer norms regarding alcohol use than African American or Latino youth. 21,22 Based on this related work, we hypothesized that Caucasian adolescents would demonstrate more susceptibility to peer influences regarding sexual behavior than their African American or Latino peers.…”
Section: Introductionmentioning
confidence: 99%